Pluralism of Religion Based on Sharia as An Anticipation of Intolerance in Muslims Majority Countries of The Southeast Asian - Syariful Alam; Happy David Pradhan (IAIN Pekalongan, 2021)
Religious pluralism is a constructive attitude, not only theological normative awareness but also social awareness, where we live in a pluralistic society in terms of religion, culture, ethnicity, and various other social diversity. In addition, religious pluralism must also be understood as a true affinity for diversity. Religious pluralism is a concept that has a broad meaning, is related to the acceptance of various religions, and is used in different ways. Pluralism aims to deconstruct absolutism, asserting relativism and underlying tolerance for differences, heterogeneity, and pluralism not only as facts that must be recognized but pluralism is seen and treated as a form of positivism, not negativism. Besides religious pluralism is also used as a unifying tool and glue for a country, both from the lower, middle and upper classes. In addition, a pluralist who promotes pluralism through pluralism must acknowledge and defend these differences, pluralism, and heterogeneity to be used as useful things. But in fact until now in the midst of society, there are still different perceptions in interpreting plurality and the term pluralism, understanding multicultural meaning based on sharia, not just mere personal perception.